Potent anti-angiogenic component in Croton crassifolius and its mechanism of action. (4th December 2015) - Huang, Weihuan; Wang, Jiajian; Liang, Yeyin; Ge, Wei; Wang, Guocai; Li, Yaolan; Yin Chung, Hau
Abstract: Ethnopharmacological relevance: The root of Croton crassifolius Geisel is traditionally used in China for the treatment of snake bites, stomach ache, sternalgia, joint pain, pharyngitis, jaundice and rheumatoid arthritis, while in Thailand, it has been used as an anticancer herbal medicine by the indigenous people. Yet, its pharmacological studies are still limited, especially towards its anticancer property. Anti-angiogenesis is a promising therapeutic strategy in the anti-cancer treatment. Previous studies have shown strong anti-angiogenic activity in the low polar fraction of the herb. Nevertheless, the potent compound which is responsible for the anti-angiogenesis, and its molecular mechanism have never been reported. Aim of the study: To determine the potent anti-angiogenic component in C. crassifolius and its molecular mechanism of action. Materials and methods: C. crassifolius was extracted using supercritical fluid extraction and steam distillation. The anti-angiogenic activities of the two extracts were evaluated in the zebrafish model by quantitative endogenous alkaline phosphatase assay. The chemical compounds in the active extract were isolated using chromatographic methods, and their structures were elucidated using different spectroscopic techniques. The content/quantity of the active compounds in this extract was determined with HPLC analysis. The molecular mechanism of the most active compound was further studied using the real-time PCR assay. Besides, its cytotoxicity on various cancer and normal cell lines was evaluated using the cell-counting kit. Results: Supercritical fluid extract (SFE) of C. crassifolius showed better anti-angiogenic activity than that of steam distillation extract (SDE). Three sesquiterpenes, namely, cyperenoic acid, 8-hydroxy-α-guaiene and (+)-guaia-l(10), ll-dien-9-one, were isolated and identified in the SFE. Among them, cyperenoic acid displayed the strongest anti-angiogenic activity by 51.7% of the control at 10 μM, while the others showed little effect. HPLC results showed that cyperenoic acid was the major component in the SFE with 9.97% (w/w). Results of the real-time PCR assay suggested that the cyperenoic acid affected multiple molecular targets related to angiogenesis including vascular endothelial growth factor (Vegfa), angpiopoietin (Angpt), and their receptors. Cytotoxicity assay showed cyperenoic acid possessed little toxicity toward cancer and normal cells. Conclusions: Cyperenoic acid is an important anti-angiogenic component present in C. crassifolius and serve as a potent inhibitor in the angiogenesis in the zebrafish embryo model. The anti-angiogenic property, but not the cytotoxicity, of C. crassifolius provides a scientific basis for its traditional use in cancer treatment. Graphical abstract: